Interventions and strategies aimed at clinical academic pathway development for nurses in the United Kingdom: A systematised review of the literature. Issue 11 (2nd February 2021) - Henshall, Catherine; Kozlowska, Olga; Walthall, Helen; Heinen, Anna; Smith, Rebecca; Carding, Paul
Abstract: Aims and objectives: To review interventions and strategies designed to progress UK clinical academic career pathways in nursing and identify barriers and facilitators to aid wider implementation. Background: For over a decade, the UK political agenda has promoted the entry of nurses into clinical academic roles. Partnerships between the National Health Service and academia are known to increase nursing recruitment, retention and quality of care. However, there remains a lack of nurses working in these partnership roles. Design: A systematised review was conducted. An electronic database search was carried out in PubMed, CINAHL, the British Nursing Database and PsychInfo for articles published between September 2006 to June 2020. A narrative approach to data synthesis was used, and the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guidelines were followed. Results: Ten papers were included in the review. The authors reported a range of programmes, pathways and toolkits. Pathway outcome measures included numbers of nurses recruited onto clinical academic programmes, clinical academic programmes completed, nursing research outputs, impact on clinical practice and impact on nursing recruitment. Barriers and facilitators to pathway development included funding, clinical and research time constraints, infrastructure, strong and strategic clinical academic leadership and effective partnership working. The quality of the included studies was mixed; more high‐quality, evidence‐based programmes need to be developed and rigorously evaluated. Conclusions: The findings can inform nursing clinical academic research pathway development internationally, by identifying key drivers for success. Sustained and cohesive implementation of clinical academic research pathways is lacking across the UK. Relevance to Clinical Practice: Strong, strategic leadership is required to enable progression of clinical academic nursing research pathway opportunities. Clinical nursing practitioners need to collaborate with external partners to enable development of clinical academic pathways within the nursing profession; this can lead to improvements in patient care and high‐quality clinical outcomes.